Gut Microbiota-Derived Propionate Regulates the Expression of Reg3 Mucosal Lectins and Ameliorates Experimental Colitis in Mice. (30th March 2020) - Bajic, Danica; Niemann, Adrian; Hillmer, Anna-Katharina; Mejias-Luque, Raquel; Bluemel, Sena; Docampo, Melissa; Funk, Maja C; Tonin, Elena; Boutros, Michael; Schnabl, Bernd; Busch, Dirk H; Miki, Tsuyoshi; et al.
Abstract: Background and Aims: Regenerating islet-derived protein type 3 [Reg3] lectins are antimicrobial peptides at mucosal surfaces of the gut, whose expression is regulated by pathogenic gut microbes via interleukin-22- or Toll-like receptor signalling. In addition to antimicrobial effects, tissue protection is hypothesized, but has been poorly investigated in the gut. Methods: We applied antibiotic-induced microbiota perturbations, gnotobiotic approaches and a dextran-sodium sulfate [DSS] colitis model to assess microbial Reg3 regulation in the intestines and its role in colitis. We also used an intestinal organoid model to investigate this axis in vitro . Results: First, we studied whether gut commensals are involved in Reg3 expression in mice, and found that antibiotic-mediated reduction of Clostridia downregulated intestinal Reg3B. A loss in Clostridia was accompanied by a significant reduction of short-chain fatty acids [SCFAs], and knock-out [KO] mice for SCFA receptors GPR43 and GPR109 expressed less intestinal Reg3B/-G. Propionate was found to induce Reg3 in intestinal organoids and in gnotobiotic mice colonized with a defined, SCFA-producing microbiota. Investigating the role of Reg3B as a protective factor in colitis, we found that Reg3B-KO mice display increased inflammation and less crypt proliferation in the DSS colitis model. Propionate decreased colitis and increased proliferation. Treatment of organoids exposed to DSS with Reg3B or propionate reversed the chemical injury with a loss of expression of the stem-cell marker Lgr5 and Olfm4. Conclusions: Our results suggest that Clostridia can regulate Reg3-associated epithelial homeostasis through propionate signalling. We also provide evidence that the Reg3–propionate axis may be an important mediator of gut epithelial regeneration in colitis.